Tools for handling the Yellow clam Mesodesma mactroides under experimental captivity conditions (INNOTEC, 2019)
Bivalve mollusks are important aquaculture and fisheries resources. On the Atlantic coast of Uruguay, the yellow clam Mesodesma mactroides has been traditionally exploited by hand. In recent years, its consumption has been notoriously valued, becoming a gastronomic product for regional restaurants. To obtain a quality product, a process of sand purification is carried out, keeping the clams in seawater tanks for short periods. However, there is no knowledge about the effects of this process or an analysis of the optimal conditions of purification. The goal of this paper was to experimentally evaluate several techniques that allow keeping M. mactroides state under laboratory conditions. Survival tests were performed to evaluate labeling, diets, types of artificial marine water (AMW), anatomical position of the organisms in captivity and substrate. The results showed that survival was not affected by the marking method and the legibility of the labels was not altered. Dry Spirulina was adequate as an alternative diet. The AMW of simpler composition and lower cost significantly increased survival after the first week of experimentation. Keeping individuals upright significantly increased survival compared to a horizontal position. These results have immediate applicability, contributing in the medium term to the development of the species in captivity.
Keywords: Mesodesma mactroides; captivity; long-term